2014
DOI: 10.1371/journal.ppat.1004478
|View full text |Cite
|
Sign up to set email alerts
|

One Small Step for a Yeast - Microevolution within Macrophages Renders Candida glabrata Hypervirulent Due to a Single Point Mutation

Abstract: Candida glabrata is one of the most common causes of candidemia, a life-threatening, systemic fungal infection, and is surpassed in frequency only by Candida albicans. Major factors contributing to the success of this opportunistic pathogen include its ability to readily acquire resistance to antifungals and to colonize and adapt to many different niches in the human body. Here we addressed the flexibility and adaptability of C. glabrata during interaction with macrophages with a serial passage approach. Conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 59 publications
7
51
0
1
Order By: Relevance
“…We also observed macrophage activation levels to be similar between the persistent WT (or persistent FKS mutant) and index WT isolate obtained from patients with persistent candidemia in the absence of antifungals. While the limited number of strains included in this study precludes a firm conclusion, our results are consistent with previous studies and suggest that the innate immune response to C. glabrata may be strain dependent, with some strains having enhanced immune evasion capabilities that could favor their persistence and the development of antifungal resistance in vivo (9,17). Further in vivo studies that include a larger number of clinical isolates with acquired echinocandin resistance will be required.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We also observed macrophage activation levels to be similar between the persistent WT (or persistent FKS mutant) and index WT isolate obtained from patients with persistent candidemia in the absence of antifungals. While the limited number of strains included in this study precludes a firm conclusion, our results are consistent with previous studies and suggest that the innate immune response to C. glabrata may be strain dependent, with some strains having enhanced immune evasion capabilities that could favor their persistence and the development of antifungal resistance in vivo (9,17). Further in vivo studies that include a larger number of clinical isolates with acquired echinocandin resistance will be required.…”
Section: Discussionsupporting
confidence: 87%
“…Direct or indirect interactions of antifungals with the host immune response have been shown to play a role in shaping their efficacy against fungal pathogens in vitro and in vivo (3,9,16,17). Similarly, acquired gene mutations conferring antifungal resistance and/or adaptive cell wall stress responses may diminish innate immune cell recognition and response, which may promote the survival and proliferation of resistant strains in vivo (11,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Di Pietro (S) 31,32 Fungal spore components determine the interaction with immune cells A. Brakhage (S) 38 Regulatory networks of C. albicans morphogenesis are complex C. D'Enfert (S) 41 Experimental evolution reveals unexpected factors of fungal virulence S. Brunke (Y) 75,76 Candida albicans produces a toxic surprise: Candidalysin J. Naglik (S) 56 Coprinopsis cinerea produces potent fungal defense effectors M. K€ unzler (S) [59][60][61] The fungal cell wall acts as immunological & drug target N. Gow (S) 70 Copper detoxification supports A. fumigatus virulence N. Osherov (Po) 77 Note. a P: plenary lecture, S: session talk, Y: young researcher presentation, Po: poster plant pathogenic fungi and might reveal natural products that are active in either host, be it plant or human.…”
Section: Take Home Message Presenter a Referencementioning
confidence: 99%
“…Some strains of C. tropicalis can also form true hyphae (Table 1), although many do not in vitro [22, 23]. Similarly, in vitro studies have shown that C. parapsilosis , C. krusei and C. glabrata do not form hyphae, though they have been reported to form pseudohyphae [2427]. C. albicans can also switch between normal white yeast cell morphology and mating-competent opaque cell growth.…”
Section: Phenotypic Differences Among Candida Species and Consequencementioning
confidence: 99%